Detection of notch1 c.7544_7545deICT mutation in chronic lymphocytic leukemia using conventional and real-time polymerase chain reaction - Bilous, N.I.; Abramenko, I.V.; Chumak, A.A.; Dyagil, I.S.; Martina, Z.V. (Experimental Oncology, 2016)
Aim: To evaluate real-time polymerase chain reaction (PCR) assay system for detection of NOTCH1 c.7541_754delCT mutation in chronic lymphocytic leukemia (CLL) patients. Material and Methods: A total of 325 CLL patients were included in the study. Screening for NOTCH1 c.7544_7545delCT was performed using conventional PCR-based amplification refractory mutation system (ARMS) method. All 33 samples harboring c.7544_7545delCT allele and 5 negative cases as control were submitted to real-time PCR. Results: Specificity and sensitivity of two PCR techniques were comparable. NOTCH1 c.7544_7545delCT mutation was found by ARMS in 10.1% of CLL patients, which is consistent with the data of other studies. However, the results of ARMS PCR in a minority of cases (2.15%) were doubtful and required reinvestigation. Real-time PCR, being less time-consuming, showed advantage in the assessment of the amplification’s specificity (using the melting curve analysis). It also allows the quantitative assessment of NOTCH1-mutated clone. Conclusion: NOTCH1 c.7544_7545delCT mutation resulting in removal of the C-terminal PEST domain, deregulation of NOTCH1-dependent signaling pathways, has negative influence on prognosis of CLL and efficiency of therapy with anti-CD20 monoclonal antibodies. Real-time PCR allows the fast and reliable detection of c.7544_7545delCT mutation and can be used for the screening of this molecular lesion in CLL patients.